2021
DOI: 10.1590/1984-3143-ar2020-0237
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parameters of lambs immunocastrated with anti-GnRH vaccine

Abstract: The objective of this study was to evaluate the testicular biometric, seminal, and plasma testosterone levels in lambs subjected to an anti-GnRH vaccine as a method of castration. Thirty entire, crossbred Santa Inês male lambs were randomly distributed into three treatment (T): T1 was the control group, with the administration of 1 mL of saline solution subcutaneously (SC); 1.0 and 0.5 mL of an anti-GnRH vaccine were administered SC in T2 and T3, respectively. Testicular biometric variables, physical and morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This method blocks the normal functioning of the hypothalamic–pituitary–gonadal axis by administering two doses of vaccine against gonadotrophin-releasing hormone (GnRH). Immunisation against GnRH results in the suppression of testosterone production and spermatogenesis [ 12 , 14 ]. While this technique has been widely adopted in pigs, there is currently no licenced product in sheep [ 13 , 14 , 15 ].…”
Section: What Is Lamb Marking?mentioning
confidence: 99%
See 1 more Smart Citation
“…This method blocks the normal functioning of the hypothalamic–pituitary–gonadal axis by administering two doses of vaccine against gonadotrophin-releasing hormone (GnRH). Immunisation against GnRH results in the suppression of testosterone production and spermatogenesis [ 12 , 14 ]. While this technique has been widely adopted in pigs, there is currently no licenced product in sheep [ 13 , 14 , 15 ].…”
Section: What Is Lamb Marking?mentioning
confidence: 99%
“…Immunisation against GnRH results in the suppression of testosterone production and spermatogenesis [ 12 , 14 ]. While this technique has been widely adopted in pigs, there is currently no licenced product in sheep [ 13 , 14 , 15 ].…”
Section: What Is Lamb Marking?mentioning
confidence: 99%
“…Gonadotropin-releasing hormone (GnRH) is a pivotal hormone of HPGA, and it regulates reproduction through the HPGA. In the past decades, GnRH has been used as an immunocastration antigen in pigs (7)(8)(9)(10)(11), calf (12)(13)(14), goats (15)(16)(17), chickens (18), horses (19)(20)(21), and some wild animals (22,23) to reduce their aggression, increasing yield, and improve the meat quality (24) or to control the reproduction of wild animals (22,23). Many studies have confirmed that GnRH has impacts on the development and functions of immune system (3,25).…”
Section: Introductionmentioning
confidence: 99%